Huellas, contextos y saberes educativos: otras maneras de ser, hacer y pensar - Muriel Valencia, Paula Andrea; Chacón Ramírez, Carlos Alberto; Moreno Parra, Marly Johana; Agudelo Vega, Sherlysaray; Gutiérrez Quimbaya, Diana Cristina; Barrios Peña, Humberto; Ávila Matamoros, Ana María; Steimbreger, Lautaro; Oliveros Tapias, Aléxander; Suárez Cortés, Anderson; Lozano Rosero, Pablo César (Universidad Santiago de Cali, 2025)
Published